2020
DOI: 10.3389/fpsyg.2020.571792
|View full text |Cite
|
Sign up to set email alerts
|

Convergent and Discriminant Validities of SCBE-30 Questionnaire Using Correlated Trait–Correlated Method Minus One

Abstract: Correlated trait-correlated method minus one was used to evaluate convergent and discriminant validity of Social Competence Behavior Evaluation questionnaire (Social Competence, Anger-Aggression, Anxiety-Withdrawal) between multiple raters. A total of 369 children (173 boys and 196 girls; M age = 55.85, SD age = 11.54) were rated by their mothers, fathers, and teachers. Results showed more convergence between parents than parent-teacher ratings. Mother-teacher share a common view of child behavior that is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Prior studies about the Turtle Program delivered in-person (Barstead et al, 2018) relied on the reports of preschool teachers and trained observers in naturalistic peer play contexts. Although parents observe qualitatively different behaviors and are more familiar with children's verbal and non-verbal cues in multiple contexts, teachers observe children in daily activities with familiar peers for a significant amount of time and they develop standards of competent behaviors based on their observation of many children of similar age and their academic knowledge pertaining to child development (Fernandes et al, 2020). Given that rating scales presuppose that informants judge how a child typically behaves in comparison with others retrospectively (Fernandes et al, 2020), observational measures are frequently considered the gold standard in intervention research (Chronis-Tuscano et al, 2015;Barstead et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies about the Turtle Program delivered in-person (Barstead et al, 2018) relied on the reports of preschool teachers and trained observers in naturalistic peer play contexts. Although parents observe qualitatively different behaviors and are more familiar with children's verbal and non-verbal cues in multiple contexts, teachers observe children in daily activities with familiar peers for a significant amount of time and they develop standards of competent behaviors based on their observation of many children of similar age and their academic knowledge pertaining to child development (Fernandes et al, 2020). Given that rating scales presuppose that informants judge how a child typically behaves in comparison with others retrospectively (Fernandes et al, 2020), observational measures are frequently considered the gold standard in intervention research (Chronis-Tuscano et al, 2015;Barstead et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This 30-item rating scale (LaFreniere and Dumas, 1996;Fernandes et al, 2020) assessed parent perceptions about the affective quality of the relationships that children aged 30-78 months establish with peers and significant adults in context. This rating scale has been widely used in different cultures (LaFreniere et al, 2002) and provides a standardized description of affect and behavior in context, discriminating behavioralemotional problems and social adjustment (LaFreniere and Dumas, 1996).…”
Section: Social Competence and Behavior Evaluation Scale-parent Versi...mentioning
confidence: 99%
“…Social Competence and Behavior Evaluation Scale (SCBE-30) [ 32 , 34 ]: The SCBE-30 has been widely used in different cultures and provides a standardized description of affect and behavior in context, discriminating behavioral-emotional problems and social adjustment [ 34 , 35 ]. This rating scale, composed of 30 items, assesses preschool teachers’ perceptions about the overall quality of child’s adaptation during peer play, in terms of three dimensions: (1) Prosocial Behavior (10 items), designed to assess a well-adjusted, flexible, emotionally mature and generally prosocial pattern of prosocial adaptation; (2) Anger-Aggression (10 items), referring to a maladaptive pattern related to externalizing behaviors, including aggressive, selfish and oppositional behaviors; and (3) Anxiety-Withdrawal (10 items), measuring a maladaptive pattern related to internalizing behaviors, including anxious, depressed, isolated and overly dependent behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Although parents are familiar with children’s cues in multiple contexts, preschool teachers observe children in daily peer interactions and develop standards of competent behaviors, based on their observation of many children of similar age [ 32 ]. Furthermore, studies found higher levels of prosocial behaviors and lower levels of aggression among girls when compared with boys and an increase in prosocial behaviors as children grow up [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation